Cyclin D1 mRNA as a molecular marker for minimal residual disease monitoring in patients with mantle cell lymphoma - Lokvenc, M; Kalinova, Marketa; Forsterova, K; Klener, P; Trneny, M; Fronkova, E; Kodet, R (Annals of hematology, 2018)
Chromosomal translocation t(11;14)(q13;q32) is a characteristic molecular marker of mantle cell lymphoma (MCL) and leads to the fusion of the immunoglobulin heavy chain enhancer-promoter with the cyclin D1 gene. Both aberrant cyclin D1 expression and underlying chromosomal aberration may be used as molecular targets for monitoring minimal residual disease (MRD). The present study aims to assess the usefulness of quantitative cyclin D1 gene expression compared to the standardised but more technologically demanding DNA-based method for immunoglobulin heavy chain (IGH) or t(11;14) clone-specific gene rearrangement quantification in a cohort of bone marrow (BM) and peripheral blood (PB) samples from patients with MCL. We simultaneously evaluated DNA-MRD and cyclin D1 expression levels in 234 samples from 57 patients. We observed that both in DNA-MRD positive and negative BM/PB pairs from the same time points the expression levels of cyclin D1 are lower in PB than in BM (median 19×, BM/PB range 0.41-352). The correlation of cyclin D1 transcript levels with DNA-MRD or with flow cytometry was good only in samples with a very high infiltration. In DNA-MRD-negative BM samples, we observed a significant heterogeneity of cyclin D1 expression (in the range of more than three orders of magnitude). This is in contrast to previous reports demonstrating the usefulness of cyclin D1 for MRD monitoring that did not use DNA-based method as a reference. In PB, the specificity of cyclin D1 expression was better due to a lower physiological background. In conclusion, we show that cyclin D1 is unsuitable for MRD monitoring in BM.
Keywords: messenger RNA; reziduální nádor; cyklin D1; regulace genové exprese u nádorů; Middle Aged; Neoplasm, Residual; mužské pohlaví; kostní dřeň; Monitoring, Physiologic; Biomarkers, Tumor; Lymphoma, Mantle-Cell; Real-time PCR; ženské pohlaví; nádorové biomarkery; RNA, Messenger; Humans; Gene Expression Regulation, Neoplastic; lidé středního věku; Bone Marrow; monitorování fyziologických funkcí; Cyclin D1; Female; Minimal residual disease; Mantle cell lymphoma; lidé; Male; lymfom z plášťových buněk